Nanotechnology-based drug delivery systems for treatment of oral cancer: a review - Calixto G (Dove Medical Press, 2014)
Giovana Calixto, Jéssica Bernegossi, Bruno Fonseca-Santos, Marlus Chorilli School of Pharmaceutical Sciences, Department of Drugs and Pharmaceuticals, São Paulo State University (UNESP), São Paulo, Brazil Abstract: Oral cancer (oral cavity and oropharynx) is a common and aggressive cancer that invades local tissue, can cause metastasis, and has a high mortality rate. Conventional treatment strategies, such as surgery and chemoradiotherapy, have improved over the past few decades; however, they remain far from optimal. Currently, cancer research is focused on improving cancer diagnosis and treatment methods (oral cavity and oropharynx) nanotechnology, which involves the design, characterization, production, and application of nanoscale drug delivery systems. In medicine, nanotechnologies, such as polymeric nanoparticles, solid lipid nanoparticles, nanostructured lipid carriers, gold nanoparticles, hydrogels, cyclodextrin complexes, and liquid crystals, are promising tools for diagnostic probes and therapeutic devices. The objective of this study is to present a systematic review of nanotechnology-based drug delivery systems for oral cancers. Keywords: targeted delivery, oral squamous cell carcinoma, oral cancer treatment